A review on Black-Scholes model - Yang, Yang (2016)
The Black-Scholes model has been served as the most fundamental model in option pricing for over four decades. Its derivation is based on ideal assumptions which are impossible in practice. Empirical evidences showed that the Black-Scholes model provides reasonable theoretical estimations of option prices most of the time; however, in some extreme situations the estimated results deviate far from observed prices. The reason of this deviation originates from the impractical assumptions. More than abundance of alternatives have been derived to complement the Black-Scholes model but the majority of them are history-fitting models. In this report, influential and remarkable theoretical extensions of the Black-Scholes model are reviewed. Each of these extensions improves the original model by relaxing certain assumption(s) and provides a pragmatic estimation of option prices.